Implementation of Sustainable Tourism Based on Bamboo Resources in Saung Angklung UDJO - Syaifudin, Arief; ., Hendarmawan; ., Sunardi; Novianti, Evi; Hariadi, Hari (Journal of Cultural Analysis and Social Change, 2026)
Bamboo is closely linked to efforts to preserve the culture of the people of West Java. As part of daily life, bamboo is used in various aspects, including traditional architecture, arts and crafts, and handicrafts. In architecture, bamboo is used to build traditional Sundanese houses, bridges, stages, and places of worship, reflecting the continued preservation of cultural heritage and traditional construction techniques. Black bamboo, the primary material for making angklung, has unique characteristics not shared by all bamboo species. This study analyzes the implementation of sustainable bamboo-based tourism at Saung Angklung Udjo, focusing on the use of black bamboo for angklung and souvenir production, and its contribution to cultural preservation and local economic development. The study covers the sustainability of raw material supply, the production process, and its impacts on environmental, socio-cultural, and economic aspects. The primary threat to the availability of black bamboo comes from land conversion for residential purposes. To address this, Saung Angklung Udjo has partnered with Perhutani in Tasikmalaya to cultivate black bamboo, reflecting a commitment to nature conservation and ecosystem protection. The study used a descriptive qualitative approach through in-depth interviews with five angklung artisans, three bamboo farmers, and two Saung managers, as well as field observations and data triangulation. The results demonstrate the integration of sustainable tourism principles through the use of bamboo as a cultural raw material and a means of environmental education, which strengthens cultural identity, stimulates the local economy, and raises environmental awareness. However, challenges remain, such as limited capital for artisans, minimal skills regeneration, and inadequate partner infrastructure (e.g., bamboo drying facilities). Although waste management and reforestation have been well-established, the implementation of a green economy needs to be strengthened through product innovation and business diversification. Recommendations include: (1) engaging the younger generation through bamboo-based education, (2) strengthening partner infrastructure, and (3) diversifying bamboo products to expand the market and increase economic and cultural value. These steps are expected to establish Saung Angklung Udjo as a model for sustainable tourism based on local resources.